Enhancing the sense of social cohesion through virtual community : a systematic review / Hamizah Sahharon, Mohd Yusof Zulkefli and Ireena Nasiha Ibnu - Sahharon, Hamizah; Zulkefli, Mohd Yusof; Ibnu, Ireena Nasiha (Faculty of Information Management, 2023)
Fostering social cohesion is thought to be the best strategy because it can be difficult to create a sense of unity in a diverse community. In social systems, social cohesion is the degree to which members of the system identify with it and feel obligated to uphold its norms, values, and beliefs. The French sociologist Emile Durkheim went into great detail about this idea, emphasising that cohesiveness needs constant upkeep, development, and adaptation. On the other hand, not much research has been done on what makes virtual communities more cohesive socially. The purpose of this systematic review is to assess and summarise the ways in which interactions among members of virtual communities can strengthen social cohesion. In order to achieve this, we retrieved articles from the Scopus and Web of Science databases and performed a systematic review. Using keyword-based filters, we reduced the number of journal articles from the initial search, which produced 337, to fourteen studies that were pertinent. By encouraging a shared identity, a sense of belonging, task commitment, social trust, and social interaction, these studies show that interactions within virtual communities not only allow users to engage in social networking but also enhance the sense of social cohesion. We anticipate that these factors will provide insightful information for upcoming initiatives to enhance social cohesion in virtual communities.